The Classroom inverted in brazilian post-graduation: an analysis of productions between 2015 and 2019 (Research, Society and Development, 2020)
This article sought to raise the state of the art of theses and dissertations, published between 2015 and 2019 in Brazil, which have as their central or secondary theme the methodological proposal of Inverted Classroom (IC). For this purpose, the following terms were searched in the virtual addresses of the Brazilian Digital Library of Theses and Dissertations (BDTD) and in the Catalog of Theses and Dissertations - CAPES: “inverted classroom”, “flipped classroom”, “inverted class”, “inverted classroom”. From this survey, 81 works were selected, available in their entirety for free online access and in Portuguese Language. Most of the listed researches  are result of researches realized during the master's degree, in public higher education institutions and from a multidisciplinary perspective. Nevertheless, there is a prevalence for experience reports of using IC in classrooms, mainly basic education and higher education. The interest in analyzing what contributions IC would bring to the relationship between teacher and students, with an emphasis on improving student performance in assessments, seems to be the central aspect that instigated the accomplishment of a significant part of the works. Finally, it was not observed in the theses and dissertations a concern with the theoretical discussion, returning the focus to the experience, from didactic commands. It shows a challenge in relation to studies about this theme because it makes it evident that it seems not to exist general analysis from given results in the individual application of IC, neither a theoretical discussion that indicate its philosophical foundations.